Derivational Morphology in English Language - Hayu Uswatun Khasanah; Ega Dwi Adis; Dewi Rukayah; Madha Vesakha; Tigor Permana (Universitas Islam Balitar, 2017)
This study deals with derivational of morphology. This research aims to discuss theunderstanding of morphology and types of morphology, this is derivational morphem,which has same aspects suffixes and prefixes and how they are categorized. Thisresearch is descriptive qualitative. The data was gained by using literature review. Theresearcher look for the data from the internet and e-book. The result of the data are; typesof derivational morphemes are derivational prefixes (-un, -dis) while derivational suffixes (-ment, -ness, -ion, -able, -less, -en, -ize, -ly)